2022
DOI: 10.32859/era.24.34.1-23
|View full text |Cite
|
Sign up to set email alerts
|

The traditional uses of plant diversity in Gokwe South District, Zimbabwe: Timber & construction, ethnoveterinary medicine, firewood & charcoal, food, tools and handicraft, religious ceremonies & rituals & other uses

Abstract: Background: Most people who reside in rural areas have over the years benefited from the utilization of forest products obtained from forests and surrounding woodlands. Both timber and non-timber forest products are important in livelihood maintenance, provision of security, reduction of poverty and malnutrition and help generate income. The aim of the study is to evaluate and document plants that are traditionally used by community in Gokwe South District, Zimbabwe and to assess their contribution to the live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…These woody species are used by local communities in five main areas of socio-economic and cultural life: energy, crafts, traditional medicine and magic, construction and food. Different studies carried out in several regions of the world have also reported the same categories of uses for woody species (Dossou et al 2012;Sop et al 2012;Moteetee et al 2019;Ouédraogo et al 2019;Mapaya et al 2022). More particularly, the use of plant species for medico-magical purposes is a common trend in certain African countries (Sop et al 2012;Lougbegnon 2019;Dossou-Yovo et al 2021;Gbesso et al 2021), South-America (Paiva de Lucena et al 2012;Alonso-Castro et al 2019), Asia (Ernst et al 2015) and European region (Mateji et al 2020).…”
Section: Endogenous Knowledge and Uses Of Woody Plantsmentioning
confidence: 85%
“…These woody species are used by local communities in five main areas of socio-economic and cultural life: energy, crafts, traditional medicine and magic, construction and food. Different studies carried out in several regions of the world have also reported the same categories of uses for woody species (Dossou et al 2012;Sop et al 2012;Moteetee et al 2019;Ouédraogo et al 2019;Mapaya et al 2022). More particularly, the use of plant species for medico-magical purposes is a common trend in certain African countries (Sop et al 2012;Lougbegnon 2019;Dossou-Yovo et al 2021;Gbesso et al 2021), South-America (Paiva de Lucena et al 2012;Alonso-Castro et al 2019), Asia (Ernst et al 2015) and European region (Mateji et al 2020).…”
Section: Endogenous Knowledge and Uses Of Woody Plantsmentioning
confidence: 85%